Utilization of E-Commerce Platform as An Effort to Increase Performance and Business Sustainability in Pandemic Times - Komala Dewi; Merry Moy Mita (Universitas Pendidikan Ganesha, 2023)
Due to the COVID-19 pandemic, the performance of MSMEs in Medan City has decreased. The use of digital platforms is one of the strategies that must be implemented by MSMEs to survive amid policies during the COVID-19 pandemic. The purpose of this study is to analyze the use of E-Commerce as an effort to increase sales and maintain the MSME business of Medan during the pandemic. The population in this study is the total number of MSMEs registered with the Medan City MSME Office, which is 1.717-MSME units. The sampling of this study uses purposive sampling with the sampling technique used in this study is non-probability sampling using the Slovin formula. The samples in this study were 323 samples. The research method uses qualitative descriptive analysis to assess the condition of natural objects or situations of research objects and understand social phenomena from the perspective of participants and quantitative for data processing using SPSS software tools version 21. The results showed that E-Commerce has an effect on improving performance and can maintain business continuity so that it can survive during the current pandemic. The implications of this research are expected that MSMEs will be able to sustainably maintain business continuity and can increase business sales.